The Issue of Hidden Hunger - Fróna, Dániel; Harangi-Rákos, Mónika (International Journal of Engineering and Management Sciences, 2019)
Mankind faces major challenges in the area of food safety and food security. In addition to the growing population, urbanization, climate change, global environmental change and economic inequality, as well as instability, have a major impact on balanced food supply. According to the WHO (2018) study, not only the elimination of hunger is a problem, but also the increase of our well-being. While 0.8 billion people suffer from a lack of available food, 33% of the global population is overweight, 30% of them are obese. In a long term our growing well-being can also be a great problem. There are three types of dietary problems that coexist in parallel: the hunger and malnutrition, the microelement deficiency, and excessive nutrition and obesity. These three health problems represent a serious burden on public health, which has to be considered in the context of food security and food safety.